Empowerment of Islamic Ethics and Javanese Hindu Ethics in the Formation of National Character - Daryono; Suparman Syukur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This research seeks to examine the strengthening of Islamic and Hindu ethics in Java, playing a pivotal role in shaping the character of Javanese society and extending influence to the broader Indonesian community. Given the dominance of Javanese traditions, particularly in societal behavior, the empowerment process unfolds through interconnection and transformation within religious activities. This process brings forth the inherent genius of the local Javanese populace, fostering a religious dimension. This empowerment occurs by emphasizing the concentration of feelings (rasa) as the basis for behavior and the objectification of Javanese people's religious beliefs. The analysis methodology adopts content analysis with a comparative approach and an anthropolinguistic perspective. The goal of this methodological approach is to unveil the mechanism for cultivating profound self-awareness in relation to others, translating acquired knowledge (kaweruh) into tangible actions as a religious model. The resulting model of religious objectification represents the local genius and behavioral characteristics of Javanese Muslims. The study reveals that the features of religious objectification, expressing the truths inherited from ancestors, transform into local wisdom with an Islamic or Hindu religious essence. This transformation is indicated by three key Javanese cultural values: harmony, functional structure, and transcendental aspects. The applicability of these three values, especially for the Surakarta and Yogyakarta areas, also serves as an identity for the ethos of religious harmony and a factor in forming the behavioral character of Javanese Muslims and may extend to influence the Indonesian people in general.